Improving Young Learner Reading Skills Through Interactive Games: A Classroom Action Research at Dynata School, Bali - Ni Luh Eka Putri Haryani; Putu Kerti Nitiasih; Eka Sulistia Dewi; Made Hery Santosa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Reading is one of the fundamental language skills that plays an important role in supporting young learners’ academic development and language acquisition. However, many elementary school students experience difficulties in understanding reading texts and achieving satisfactory reading performance. The study aimed to improve students’ reading skills through the implementation of Interactive Games in English language learning. Interactive Games were selected because they provide an engaging, student-centered, and motivating learning environment that can increase students’ participation and comprehension during reading activities. The study employed Classroom Action Research consisting of two cycles, namely Cycle I and Cycle II. The participants were 30 students. Data were collected through reading tests, observation sheets, and documentation. The findings revealed that the implementation of Interactive Games successfully improved studen’ reading skills. In the pre-cycle, only 11 students (36.67%) achieved the Minimum Completion Criteria with an average score of 59.3. After the implementation of Interactive Games in Cycle I, the number of students achieving the KKM increased to 16 students (53.3%) with an average score of 67.3. Furthermore, in Cycle II, 24 students (80%) achieved the KKM with an average score of 71.3. The observation results also showed that students became more active, motivated, and engaged in the learning process. The improvement from 36.67% to 80% of students achieving the KKM indicates that Interactive Games contributed substantially to students’ reading achievement and classroom participation. These findings indicate that Interactive Games can create an enjoyable learning environment and effectively improve students’ reading achievement. Therefore, Interactive Games are recommended as an innovative teaching strategy to enhance students’ reading skills and participation in English language learning. This study contributes to the growing body of research on game-based language learning by providing empirical evidence of the effectiveness of Interactive Games in improving young learners’ reading skills in an elementary school context.